Sediment and carbon dynamics during an episodic flood in an intermittent river. Issue 10 (23rd October 2022) - Liu, Xinyu; Lu, Xixi; Yu, Ruihong; Sun, Heyang; Li, Yuan; Qi, Zhen; Xue, Hao; Zhang, Zhuangzhuang; Cao, Zhengxu; Liu, Tingxi; Lu, Changwei
Abstract: The contribution of intermittent rivers and ephemeral streams (IRES) to the global carbon cycle has largely been overlooked. Flood events can impact hydrological processes, carbon (C) transport, and carbon dioxide (CO2 ) emissions. This study monitored river flow and sediment concentrations in an intermittent river during a flood event. Water samples were measured for water quality factors and C transport indices. CO2 partial pressure (pCO2 ) and CO2 flux ( F CO2 ) were also analyzed. Remote sensing data were used to analyze soil erosion in the basin. Results indicate that the total sediment load from the flood was approximately 5503.1 t, with sediment concentrations showing a direct relationship with flow discharge. By completing a hysteresis loop and soil erosion level analysis, soil erosion from the river source and runoff surface scour were found to be the primary sources of sediment. The flood significantly increased particulate organic carbon and decreased dissolved organic carbon. During the flood, pCO2 ranged between 669 and 1229 ppm, indicating that the IRES served as a carbon source, with pH and total dissolved solids being the main influencing factors. The F CO2 varied between 20.16 and 568.33 mg m −2 h −1 and revealed a significant positive correlation with pCO2 . After the flood ended, CO2 emissions increased and remained high for a long time. The study findings have substantial implications for IRES responses to extreme flood events, which are predicted to increase in intensity under climate change.